Piezoresistor Sensor Fabrication by Direct Laser Writing on Hydrogenated Amorphous Silicon. Issue 1594 (13th March 2014) - Alpuim, P.; Cerqueira, M.F.; Junior, G.; Gaspar, J.; Borme, J.
ABSTRACT In this paper we report on the 532 nm Nd:YAG laser-induced crystallization of 10 nm thick boron-doped hydrogenated amorphous silicon thin films deposited on flexible polyimide and on rigid oxidized silicon wafers by hot-wire or by plasma-enhanced chemical vapor deposition. The dark conductivity increased from ∼10-7 Ω-1cm-1, in the as-deposited films, to ∼10 and 50 Ω-1cm-1 after laser irradiation, on rigid and flexible substrates, respectively. Depending on type of substrate, laser power and fluence, a Raman crystalline fraction between 55 and 90 % was measured in HWCVD films, which was higher than observed in rf-PECVD films (35-55 %). Crystallite size remained small in all cases, in the range 6-8 nm. Due to a very high conductivity contrast (>7 orders of magnitude) between amorphous and crystallized regions, it was possible to define conductive paths in the a-Si:H matrix, by mounting the sample on a X-Y software-controlled movable stage under the laser beam, with no need for the usual lithography steps. The resistors scribed by direct laser writing had piezoresistive properties, with positive gauge factor ∼1. The details of the laser interaction process with the Si film were revealed by scanning electron microscopy imaging.